2022
DOI: 10.5194/hess-2022-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating downscaling methods of GRACE data: a case study over a fractured crystalline aquifer in South India

Abstract: Abstract. GRACE (Gravity Recovery and Climate Experiment) and its follow-on mission have provided since 2002 monthly anomalies of total water storage (TWS), which are very relevant to assess the evolution of groundwater storage (GWS) at global and regional scale. However, the use of GRACE data for groundwater irrigation management is limited by their coarse (≃ 300 km) resolution. The last decade has thus seen numerous attempts to downscale GRACE data at higher – typically several tens of km – resolution and to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Shukla et al opinioned GRACE mission, widely used for monitoring groundwater storage change, could be utilized to get information on the exact amount of water above or below the surface of the Earth that may be used to counteract such situations of the water crisis [20]. Claire Pasca et al suggested advanced methods to improve the data quality close to the measured values [21]. The downscaling performance is evaluated by comparing the downscaled versus in situ GWS data over 38 pixels at 0.50 resolution.…”
Section: Alexander Developed Artificial Neural Network (Ann) Modelsmentioning
confidence: 99%
“…Shukla et al opinioned GRACE mission, widely used for monitoring groundwater storage change, could be utilized to get information on the exact amount of water above or below the surface of the Earth that may be used to counteract such situations of the water crisis [20]. Claire Pasca et al suggested advanced methods to improve the data quality close to the measured values [21]. The downscaling performance is evaluated by comparing the downscaled versus in situ GWS data over 38 pixels at 0.50 resolution.…”
Section: Alexander Developed Artificial Neural Network (Ann) Modelsmentioning
confidence: 99%